Adsorbent composition and method for producing the same
Patent Information
- Application Number
- JP2024212492
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-12-06
- Filing Date
- 2024-12-05
- Publication Date
- 2026-10-22
- Estimated Expiration
- 2044-12-05
AI Technical Summary
【0007】 本開示の吸着剤組成物は、複数のタイプの吸着装置に用いることができる。本開示の部材および利点がより明らかかつ理解し易くなるよう、以下に各種実施形態を挙げ、添付の図面と対応させながら、詳細に説明する。
Smart Images

Figure 0007939988000004 
Figure 0007939988000005 
Figure 0007939988000006
Abstract
Description
[Technical Field]
[0001] This disclosure relates to adsorbent compositions and methods for producing the same, and more particularly to adsorbent compositions containing particles with different heat dissipation amounts and methods for producing the same. [Background technology]
[0002] Adsorbents are commonly used as packing materials in reactors, such as fixed-bed reactors (also called packed reactors), to adsorb and desorb gases such as carbon dioxide. However, during adsorption and desorption, localized high temperatures in the reactor can cause the adsorbent to degrade, leading to reduced adsorption efficiency and loss of effectiveness of the adsorbent composition. Furthermore, adding dispersion materials as part of the packing material can cause layering during adsorption and desorption due to density differences, potentially reducing adsorption efficiency. Additionally, the dispersion material occupies a volume within the reactor, reducing the total amount of adsorbent packed, which in turn reduces the total adsorption capacity of the system. [Overview of the project] [Problems that the invention aims to solve]
[0003] Therefore, while existing adsorbent compositions and their manufacturing methods meet the requirements of their respective intended applications, they do not perfectly satisfy all requirements in every aspect. Consequently, there are still several problems that need to be overcome regarding adsorbent compositions and their manufacturing methods. [Means for solving the problem]
[0004] The adsorbent compositions of this disclosure may contain adsorbent particles with different heat dissipation rates, which can increase adsorption efficiency and / or prevent the adsorbent composition from losing its effectiveness. Adsorption efficiency may include balance adsorption amount, working adsorption amount, balance adsorption recovery, and working adsorption recovery.
[0005] In several embodiments, an adsorbent composition is provided. The adsorbent composition comprises 100 parts by weight of a first particle and 3 to 450 parts by weight of a second particle. The first particle is a base particle having an amino group and has a first heat release amount. The second particle is a base particle having an amino group and an epoxy group and has a second heat release amount. The first heat release amount is greater than 90 J / g and 130 J / g or less, and the second heat release amount is 35 J / g or more and 90 J / g or less.
[0006] In some embodiments, a method for producing an adsorbent composition is provided. The production method includes the step of preparing first particles, the first particles being base particles having amino groups, and the first particles having a first heat dissipation amount. The first heat dissipation amount is greater than 90 J / g and 130 J / g or less. Second particles are prepared, the second particles being base particles having amino groups and epoxy groups, and the second particles having a second heat dissipation amount. The second heat dissipation amount is 35 J / g or more and 90 J / g or less. The first particles and the second particles are mixed to obtain an adsorbent composition. The amount of the first particles is 100 parts by weight, and the amount of the second particles is 3 to 450 parts by weight.
[0007] The adsorbent compositions of this disclosure can be used in several types of adsorption devices. Various embodiments of this disclosure are described below in detail with reference to the accompanying drawings, so that the components and advantages of this disclosure may be made clearer and easier to understand.
[0008] The present disclosure can be further fully understood from the following detailed description when read in conjunction with the accompanying drawings. It should be noted that, following standard practices in the industry, the various components are not drawn to equal proportions. In practice, the dimensions of each component may be arbitrarily enlarged or reduced for the sake of clarity. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] [Figure 1] 1 shows a flowchart of a method for producing an adsorbent composition according to some embodiments of the present disclosure. [Figure 2] FIG. 3 shows a Fourier-transform infrared spectroscopy (FTIR) analysis graph according to some embodiments of the present disclosure. [Figure 3] FIG. 4 is a diagram of a breakthrough curve according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION
[0010] Hereinafter, the adsorbent composition of each embodiment in the present disclosure and the production method thereof will be described in detail. In the following description, it should be understood that a plurality of different embodiments are presented as different aspects of some embodiments of the present disclosure. The specific components and arrangement modes described below are merely for the purpose of concisely and clearly describing some embodiments of the present disclosure. Naturally, these are merely illustrative and are not intended to limit the present disclosure. In addition, in different embodiments, reference numerals for similar and / or corresponding components may be used to indicate similar and / or corresponding components to clearly describe the present disclosure. However, the use of these reference numerals for similar and / or corresponding components is merely for the purpose of concisely and clearly describing some embodiments of the present disclosure, and does not represent any correlation between the different embodiments and / or structures referred to.
[0011] Ordinal numbers used in the specification and claims, for example, terms such as "first", "second", etc., are used to modify constituent elements, and do not by themselves imply or indicate that there is any preceding ordinal number for that (or those) constituent element(s), nor do they represent the order of one constituent element relative to another, or the order in a manufacturing method. It should be understood that these ordinal numbers are used solely to clearly distinguish one named constituent element from another constituent element bearing the same name. The same terms may not be used in the claims and the specification; for example, a first constituent element in the specification may be a second constituent element in the claims.
[0012] In the present text, terms such as "approximate", "about", and "substantially" generally mean being within 10%, or within 5%, or within 3%, or within 2%, or within 1%, or within 0.5% of a given value or range. Even where no particular description indicating that a given number is an approximate number, i.e., "approximate", "about", or "substantially", is provided, the meanings of "approximate", "about", and "substantially" may be encompassed. The expression "a range is between a first numerical value and a second numerical value" or "a first numerical value to a second numerical value" means that the range includes the first numerical value, the second numerical value, and all other numerical values therebetween. Furthermore, a certain error exists between any two numerical values used for comparison. When a first numerical value is said to be equal to a second numerical value, this means that an error of about 10%, or within 5%, or within 3%, or within 2%, or within 1%, or within 0.5% may exist between the first numerical value and the second numerical value. The expression "the value of the ratio between a first numerical value and a second numerical value" represents the value of the ratio (first numerical value / second numerical value) when the first numerical value is taken as the numerator and the second numerical value is taken as the denominator. The expression "the ratio of a first numerical value to a second numerical value" represents the ratio of the first numerical value:the second numerical value.
[0013] In the following specification and claims, terms such as “includes,” “contains,” and “have” are open-ended terms and should therefore be interpreted as “contains, but is not limited to.” Accordingly, where the terms “includes,” “contains,” and / or “have” are used in this disclosure, they indicate the presence of a corresponding component, region, step, operation, and / or element, but do not exclude the presence of one or more corresponding components, regions, steps, operations, and / or elements.
[0014] It should be understood that the embodiments described below can be modified to complete other embodiments by substituting, rearranging, and combining components from multiple different embodiments, without departing from the spirit of this disclosure. Within each embodiment, components can be used in any combination, as long as it does not contradict or conflict with the spirit of the invention.
[0015] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as those commonly understood by those skilled in the art. Unless specifically defined in the embodiments of this disclosure, these terms, for example, those defined in commonly used dictionaries, should be understood to have meanings consistent with the relevant art and the background or context of this disclosure, and should not be interpreted in an idealized or overly formal manner.
[0016] In the following description, the "heat release amount" of adsorbed particles refers to the amount of heat released (joules (J)) per gram (g) of adsorbed particles in a gas environment of 10% volume percent (vol%) carbon dioxide (90 vol% inert gas). Therefore, the unit of the heat release amount of adsorbed particles can be expressed as J / g, and the numerical value is the pure value of the heat released. Specifically, when the "heat release amount" of adsorbed particles is described as (AJ / g) in the following description, it means that the absolute value of heat released by each gram of adsorbed particles into the gas environment is A joules. Furthermore, the heat release amount of adsorbed particles can be changed depending on the composition of the gas environment. For example, if the same adsorbed particles are placed in different gas environments, the heat release amount of the adsorbed particles will change. The heat release amount of adsorbed particles can be measured using a thermogravimetric analyzer (TGA) and a differential scanning calorimetry (DSC).
[0017] In the following description, the "average heat release amount" of the adsorbent composition is calculated based on the weight ratio of different particles in the adsorbent composition. For example, the average heat release amount may be the sum of the product of the weight parts of the first particle (a, dimensionless) and the heat release amount of the first particle (AJ / g), and the product of the weight parts of the second particle (b, dimensionless) and the heat release amount of the second particle (BJ / g), divided by the total weight parts of the first and second particles ((a × A + b × B) / (a + b)). For example, the average heat dissipation may be the sum of the product of the weight percentage of the first particle in the adsorbent composition (a wt%) and the heat dissipation of the first particle (AJ / g), and the product of the weight percentage of the second particle in the adsorbent composition (b wt%) and the heat dissipation of the second particle (BJ / g) (a wt% × A + b wt% × B).
[0018] Please refer to Figure 1, which shows a flowchart of a method for producing an adsorbent composition according to some embodiments of the present disclosure.
[0019] In step S1, a first particle is prepared. In some embodiments, the first particle is a base particle having an amino group, and the first particle has a first heat dissipation. In some embodiments, the first heat dissipation may be greater than 90 J / g and less than or equal to 130 J / g. For example, the first heat dissipation may be 90.1 J / g, 100 J / g, 110 J / g, 111 J / g, 112 J / g, 112.9 J / g, 113 J / g, 114 J / g, 115 J / g, 119.6 J / g, 120 J / g, 130 J / g, or any number between these values or a range of any number. For example, the first heat dissipation amount may be 90.1 J / g to 130 J / g, 100 J / g to 119.6 J / g, or 110 J / g to 115 J / g, but the disclosure is not limited thereto.
[0020] In some embodiments, the step of preparing the first particles is: Step a involves mixing base particles and a metal chelating agent to obtain a first powder, Step b involves mixing a material containing amino groups with a first powder to obtain a second powder, Step c involves mixing the second powder with the adhesive to obtain the first particles. It may include.
[0021] In some embodiments, the base particle may include, but is not limited to, silicon dioxide, aluminum oxide, titanium oxide, calcium silicate, carbon nanotubes, activated carbon, acetate fiber, analogues thereof, or combinations thereof. In some embodiments, the base particle may be a porous or non-porous powder material. In some embodiments, the particle size of the base particle may be between 1 μm and 500 μm. For example, the particle size of the base particle may be 1 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, or any number between these numbers or a range of any number thereto, but is not limited to, this disclosure.
[0022] In some embodiments, a metal chelating agent is used to chelate metal elements in base particles, preventing metal ions in the base particles from becoming impurities and causing disturbances. In some embodiments, the metal chelating agent may be an inorganic metal chelating agent, an organometallic chelating agent, or a combination thereof. In some embodiments, the inorganic metal chelating agent may include sodium phosphate.
[0023] In some embodiments, the amine group material may include compounds or polymers having primary amine groups (-NH2), secondary amine groups (-NHR), or tertiary amine groups (-NR2). In some embodiments, the molecular weight of the amine group material may be 500 or more and less than 10,000. For example, the molecular weight of the amine group material may be 500-9999, 3000-9999, 5000-8000, 600-3000, or 800-1200, but this disclosure is not limited thereto. In some embodiments, the amine group material may include linear polyethyleneimine (PEI), branched polyethyleneimine, or a combination thereof, but this disclosure is not limited thereto.
[0024] In some embodiments, the ratio of the weight of the amino group-containing material to the weight of the base particle in the first particle may be between 0.5 and 0.75. For example, the ratio of the weight of the amino group-containing material to the weight of the base particle in the first particle may be 0.5, 0.55, 0.6, 0.64, 0.65, 0.7, 0.75, or any number between these numbers or a range of any number, but the disclosure is not limited thereto. For example, the ratio of the weight of the amino group-containing material to the weight of the base particle in the first particle may be between 0.55 and 0.7 or between 0.6 and 0.65, but the disclosure is not limited thereto.
[0025] In some embodiments, the adhesive may include, but is not limited to, nitrile butadiene rubber latex, chloroprene rubber, styrene-butadiene rubber, analogues thereof, or combinations thereof. In some embodiments, the weight of the adhesive is 0.5% to 30% of the total weight of the first particles. For example, the weight of the adhesive may be 0.5%, 1%, 4%, 4.1%, 5%, 10%, 20%, 30%, or any number between these numbers or a range of any number between them, but is not limited to the disclosure.
[0026] In step S2, a second particle is prepared. In some embodiments, the second particle is a base particle having an amino group and an epoxy group, and the second particle has a second heat dissipation. In some embodiments, the second heat dissipation may be 35 J / g or more and 90 J / g or less. For example, the second heat dissipation may be 35 J / g, 40 J / g, 45 J / g, 45.1 J / g, 46 J / g, 50 J / g, 55 J / g, 60 J / g, 63 J / g, 63.3 J / g, 64 J / g, 65 J / g, 69 J / g, 69.2 J / g, 70 J / g, 75 J / g, 76 J / g, 76.3 J / g, 77 J / g, 80 J / g, 85 J / g, 90 J / g, or any number between these numbers or a range of any number. For example, the second heat dissipation amount may be 35 J / g to 90 J / g, 40 J / g to 85 J / g, or 45 J / g to 80 J / g, but the disclosure is not limited thereto.
[0027] In some embodiments, the second particle may include a third particle and a fourth particle. The third particle may have a third heat dissipation amount, and the fourth particle may have a fourth heat dissipation amount different from the third heat dissipation amount. In some embodiments, the third heat dissipation amount may be greater than 65 J / g and less than or equal to 90 J / g. For example, the third heat dissipation amount may be 66 J / g, 69 J / g, 69.2 J / g, 70 J / g, 75 J / g, 76 J / g, 76.3 J / g, 77 J / g, 80 J / g, 85 J / g, 90 J / g, or any number between these values or a range of any number, but the disclosure is not limited thereto. For example, the third heat dissipation amount may be 66 J / g to 90 J / g, 66 J / g to 80 J / g, or 69 J / g to 77 J / g, but the disclosure is not limited thereto. In some embodiments, the fourth heat dissipation amount may be 35 J / g or more and less than 65 J / g. For example, the fourth heat dissipation amount may be 35 J / g, 40 J / g, 45 J / g, 45.1 J / g, 46 J / g, 50 J / g, 55 J / g, 60 J / g, 63 J / g, 63.3 J / g, 64.9 J / g, or any number between these values or a range of any number, but the disclosure is not limited thereto. For example, the fourth heat dissipation amount may be 35 J / g to 64.9 J / g, 40 J / g to 64 J / g, or 45 J / g to 64 J / g, but the disclosure is not limited thereto.
[0028] In some embodiments, the step of preparing a second particle is: Step d involves mixing a material containing an amino group with an epoxide to obtain a solution, Step e involves mixing the solution with the first powder to obtain the third powder, Step f involves mixing the third powder with the adhesive to obtain the second particles. It may include.
[0029] In some embodiments, the epoxide may include, but is not limited to, ethylene oxide, propylene oxide, 1,2-butylene oxide, 1,2-epoxypentane, 1,2-epoxyhexane, analogues thereof, or combinations thereof. In some embodiments, the ratio of the weight of the epoxide to the weight of the amino group-containing material may be greater than 0. In some embodiments, the ratio of the weight of the epoxide to the weight of the amino group-containing material is between 0.01 and 0.8. For example, the ratio may be 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.58, 0.588, 0.59, 0.594, 0.6, 0.7, 0.8, or any number between these numbers or a range of any number.
[0030] In some embodiments, third and fourth particles can be obtained by adjusting the ratio of the weight of the epoxide to the weight of the amino group-containing material. For example, in the third particles, the ratio of the weight of the epoxide to the weight of the amino group-containing material may be 0.4 to 0.7, 0.5 to 0.6, or 0.594, but the disclosure is not limited thereto. For example, in the fourth particles, the ratio of the weight of the epoxide to the weight of the amino group-containing material may be 0.4 to 0.7, 0.5 to 0.6, or 0.594, but the disclosure is not limited thereto.
[0031] In some embodiments, the ratio of the weight of the amino group-containing material to the weight of the base particle in the second particle may be between 0.2 and 0.65. For example, the ratio of the weight of the amino group-containing material to the weight of the base particle in the second particle may be 0.2, 0.25, 0.3, 0.31, 0.32, 0.33, 0.35, 0.4, 0.45, 0.5, 0.51, 0.52, 0.55, 0.6, 0.64, 0.65, or any number between these numbers or a range of any number, but the disclosure is not limited thereto. For example, the ratio of the weight of the amino group-containing material to the weight of the base particle in the second particle may be between 0.2 and 0.55, or between 0.25 and 0.53, but the disclosure is not limited thereto.
[0032] In some embodiments, third and fourth particles can be obtained by adjusting the ratio of the weight of the amino group-containing material to the weight of the base particles. For example, in the third particles, the ratio of the weight of the amino group-containing material to the weight of the base particles may be 0.45 to 0.65 or 0.5 to 0.55, but the disclosure is not limited thereto. For example, in the fourth particles, the ratio of the weight of the amino group-containing material to the weight of the base particles may be 0.2 to 0.45, 0.25 to 0.4, or 0.3 to 0.35, but the disclosure is not limited thereto.
[0033] In step S3, the first particles and the second particles are mixed to obtain an adsorbent composition. In some embodiments, the first particles may be 100 parts by weight, and the second particles may be 3 to 450 parts by weight. For example, the parts by weight of the second particles may be 3, 4, 4.16, 5, 10, 13.63, 50, 100, 108.37, 125, 132.65, 150, 175, 200, 225, 250, 257.14, 275, 300, 325, 334.7, 350, 375, 400, 425, 450, or any number between these numbers or a range of any number, but the disclosure is not limited thereto. If the parts by weight of the second particles is less than 3, the adsorbent composition may degrade due to thermal breakdown during adsorption and desorption. If the weight of the second particle is greater than 450, the adsorption capacity of the adsorbent composition may be excessively low.
[0034] In some embodiments, the weight of the first particles is 20% to 90% of the total weight of the adsorbent composition, and the weight of the second particles is 10% to 80% of the total weight of the adsorbent composition. For example, the weight of the first particles may be 20%, 23%, 28%, 30%, 40%, 48%, 50%, 60%, 70%, 80%, 88%, 90%, or any number between these values, or a range of any number, but the disclosure is not limited thereto. If the weight of the first particles accounts for more than 80% of the total weight of the adsorbent composition, the adsorbent composition may degrade due to thermal breakdown during adsorption and desorption. If the weight of the first particles accounts for less than 20% of the total weight of the adsorbent composition, the adsorption capacity of the adsorbent composition may be excessively low. In some embodiments, the ratio of the weight of the first particles to the weight of the second particles is 20-90:10-80. For example, the ratio of the weight of the first particle to the weight of the second particle may be 20-50:50-80.
[0035] In some embodiments, the second particle may contain 0 to 330 parts by weight of the third particle and 0 to 150 parts by weight of the fourth particle, and the third and fourth particles may not be present in 0 parts by weight at the same time. In other words, the second particle may contain at least the third or fourth particle. For example, the parts by weight of the third particle may be 0, 2, 2.08, 2.27, 4.65, 5, 10, 11.36, 20, 50, 100, 104.2, 125, 150, 175, 200, 225, 250, 275, 300, 325, 326, 330, or any number between these numbers or a range of any number. For example, the parts by weight of the fourth particle may be 0, 2, 2.08, 2.27, 4.17, 5, 7.14, 8.7, 10, 11.36, 25, 50, 75, 80, 100, 125, 128, 150, or any number between these numbers or a range of any number. However, the disclosure is not limited thereto. If the parts by weight of the third particle is greater than 330, or the parts by weight of the fourth particle is greater than 150, the adsorption capacity of the adsorbent composition may be excessively low.
[0036] In some embodiments, the average heat dissipation of the adsorbent composition may be 65 J / g or more and 120 J / g or less. For example, the average heat dissipation of the adsorbent composition may be 65 J / g to 119.9 J / g, 70 J / g to 115 J / g, 75 J / g to 110 J / g, or 80 J / g to 105 J / g, but the disclosure is not limited thereto. If the average heat dissipation of the adsorbent composition is greater than 120 J / g, the adsorbent composition may deteriorate due to thermal breakdown during adsorption and desorption. If the average heat dissipation of the adsorbent composition is less than 65 J / g, the adsorption capacity of the adsorbent composition may be excessively low.
[0037] In some embodiments, the first particles may contain amino groups, and the second particles may contain amino groups and epoxy groups. In some embodiments, the content of amino groups in the first particles may be greater than the content of amino groups in the second particles, so that the adsorption amount of carbon dioxide by the first particles can be higher than the adsorption amount of carbon dioxide by the second particles. In some embodiments, the third particles and the fourth particles may each contain amino groups and epoxy groups, and the content of amino groups in the third particles may be greater than the content of amino groups in the fourth particles.
[0038] The more amino groups in the adsorption particles, the easier it is to adsorb (capture) carbon dioxide, and the higher the carbon dioxide adsorption amount becomes. Since epoxy groups cause a crosslinking reaction with amino groups, the content of amino groups capable of adsorbing carbon dioxide decreases. Therefore, the more epoxy groups in the adsorption particles, the more difficult it is for the adsorption particles to adsorb carbon dioxide, and the carbon dioxide adsorption amount decreases. Accordingly, the higher the carbon dioxide adsorption amount, the more likely the exothermic reaction is to occur, leading to at least a local temperature rise in the reactor, which will degrade the adsorption particles. For example, if it can be observed that the appearance of the adsorption particles changes from white to yellow, it indicates degradation of the adsorption particles.
[0039] In some embodiments, the density of the first particles and the second particles may be 0.3 g / cm 3 ~0.8 g / cm 3 . For example, the density of the first particles and the second particles may be 0.3 g / cm 3 , 0.4 g / cm 3 , 0.5 g / cm 3 , 0.58 g / cm 3 , 0.6 g / cm 3 , 0.63 g / cm 3 , 0.65 g / cm 3 , 0.67 g / cm 3 , 0.7 g / cm 3 , 0.72 g / cm 3 , 0.8 g / cm 3, or any number between these numbers or a range of numbers consisting of any number, but the disclosure is not limited thereto. In some embodiments, the density of the first particle is 0.58 g / cm³ 3 ~0.65g / cm 3 The density of the second particle is 0.6 g / cm³. 3 ~0.72g / cm 3 This may be the case. In some embodiments, the density of the third particle is 0.67 g / cm³. 3 ~0.72g / cm 3 The density of the fourth particle is 0.6 g / cm³. 3 ~0.63g / cm 3 That's fine.
[0040] In some embodiments, the adsorbent compositions of the Disclosure can be used to adsorb and desorb gases. For example, the gas may be carbon dioxide or other suitable gases, but the Disclosure is not limited thereto. In some embodiments, the adsorbent compositions of the Disclosure can serve as packing material for a reactor. For example, the reactor may be a fixed-bed reactor or other suitable reactor, but the Disclosure is not limited thereto.
[0041] The following description will explain, with examples, the method for producing the adsorbent composition.
[0042] In some embodiments, the base particles in step a are silicon dioxide powder with an average particle size of 35 μm, and the metal chelating agent is a phosphate. Specifically, moisture is removed from the silicon dioxide powder at a temperature of 100°C. The phosphate is dissolved in water and mixed and stirred with the silicon dioxide powder from which the moisture has been removed. After that, moisture is removed using a vacuum oven at a temperature of 100°C to obtain the first powder.
[0043] In some embodiments, the amino group-containing material in step b is polyethyleneimine (molecular weight: 1200). Specifically, polyethyleneimine is added to a solvent (e.g., alcohol) to obtain a polyethyleneimine solution. The polyethyleneimine solution and the first powder are mixed and stirred, then dried to obtain a second powder. Drying is carried out under negative pressure at a temperature of 40°C to 50°C.
[0044] In some embodiments, the adhesive in step c is chloroprene rubber (containing about 50 wt% of a polymer of 2,3-dichloro-1,3-butadiene and 2-chloro-1,3-butadiene, or about 45 wt% of a polymer of 2-methyl-2-propenoic acid and 2-chloro-1,3-butadiene). Specifically, the second powder is moistened with deionized water, the adhesive is added and mixed and stirred, and then the moisture is removed under vacuum at a temperature of 105°C to obtain the first particles. In some embodiments, granulation can be further carried out using a syringe or granulator. In some other embodiments, the granulation step can be omitted.
[0045] In some embodiments, the epoxide in step d is butylene oxide. Specifically, butylene oxide is added dropwise to the polyethyleneimine solution and uniformly stirred at room temperature (e.g., 25°C) to allow the crosslinking reaction to proceed and obtain a clear, transparent solution.
[0046] In some embodiments, in step e, a clear liquid and the first powder were mixed and stirred to obtain a milky white liquid containing a white suspension. The milky white liquid was dried to obtain a third powder. The milky white liquid can be dried under negative pressure at a temperature of 40°C to 50°C.
[0047] In some embodiments, during step f, the third powder was moistened with deionized water, then the adhesive was added and mixed and stirred, and the moisture was removed under vacuum and at a temperature of 105°C to obtain the second particles. In some embodiments, a granulation step may be further carried out, or the granulation step may be omitted.
[0048] Therefore, this disclosure allows for the adjustment of the amount of heat dissipated when adsorbing particles adsorb and / or desorb carbon dioxide by adjusting the ratio of polyethyleneimine (providing amino groups) to butylene oxide (providing epoxy groups) (amino group-epoxy group modified mass) and the ratio of polyethyleneimine to silicon dioxide powder (amount of amino group coating on the surface of silicon dioxide powder). Thus, adsorbing particles with similar densities but different heat dissipation amounts can be obtained.
[0049] In some embodiments, the adsorbent composition comprises first particles and second particles, and the second particles comprises third particles and fourth particles.
[0050] First particle: 50 g of porous silicon powder was heated and dried at 100°C to remove moisture, then mixed and stirred with 260 g of 0.79 wt.% sodium phosphate aqueous solution for 2 hours, and again vacuum-dried at 100°C to remove moisture and obtain a white powder. 94 g of 34 wt.% polyethyleneimine aqueous solution was prepared and mixed and stirred with the white powder for 2 hours, and the solution was removed under negative pressure at 40°C to obtain an amino group-modified white powder. 5 g of the amino group-modified white powder was taken, moistened with deionized water, and then 0.65 g of adhesive was added and mixed and stirred. Next, moisture was removed under vacuum at 105°C and heated and dried to obtain a white first particle with high heat dissipation and high carbon dioxide adsorption capacity. The ratio of the weight of the amino group-containing material to the weight of the base particles is approximately 0.64.
[0051] Third particle: 50 g of porous silicone powder was heated and dried at 100°C to remove moisture, then mixed and stirred with 260 g of 0.79 wt.% sodium phosphate aqueous solution for 2 hours, and again vacuum-dried at 100°C to remove moisture and obtain a white powder. 94 g of 34 wt.% polyethyleneimine aqueous solution was prepared, 19 g of butylene oxide was added dropwise, and the mixture was stirred at 25°C for 20 hours. Then, it was further mixed and stirred with the white powder for 2 hours, and the solution was removed under negative pressure at 40°C to obtain an amino group-epoxy group modified white powder. 5 g of the amino group-epoxy group modified white powder was taken, moistened with deionized water, and then 0.65 g of adhesive was added and mixed and stirred. Next, moisture was removed under vacuum at 105°C and heated and dried to obtain a third white particle with moderate heat dissipation and moderate carbon dioxide adsorption. The ratio of the weight of the amino group-containing material to the weight of the base particles is approximately 0.64. The ratio of the weight of the epoxide to the weight of the material containing amino groups is approximately 0.594.
[0052] Fourth particle: 50 g of porous silicon powder was heated and dried at 100°C to remove moisture, then mixed and stirred with 260 g of 0.79 wt.% sodium phosphate aqueous solution for 2 hours, and further vacuum-dried at 100°C to remove moisture and obtain a white powder. 47 g of 34 wt.% polyethyleneimine aqueous solution was prepared, 9.5 g of butylene oxide was added dropwise, and the mixture was stirred at 25°C for 20 hours. Then, it was further mixed and stirred with the white powder for 2 hours, and the solution was removed under negative pressure at 40°C to obtain an amino group-epoxy group modified white powder. 5 g of the amino group-epoxy group modified white powder was taken, moistened with deionized water, and then 0.65 g of adhesive was added and mixed and stirred. Next, moisture was removed under vacuum at 105°C and heated and dried to obtain a white fourth particle with low heat dissipation and low carbon dioxide adsorption. The ratio of the weight of the amino group-containing material to the weight of the base particles is approximately 0.32. Therefore, the amount of amino group coverage on the surface of the fourth particle may be less than the amount of amino group coverage on the surface of the third particle. The ratio of the weight of the epoxide to the weight of the material containing amino groups is approximately 0.594. Therefore, the amino group-epoxy group modification mass of the third particle may be similar to that of the amino group-epoxy group modification mass of the fourth particle.
[0053] Please refer to Figure 2. It shows Fourier transform infrared (FTIR) spectroscopy analysis diagrams for several embodiments of this disclosure. Adsorbed particles were placed in a 105°C oven to remove moisture, then ground and analyzed by FTIR. The test wavelength was 4000 cm⁻¹. -1 ~400cm -1 As shown in Figure 2, the first, third, and fourth particles were 1564 cm². -1 ~1587cm -1 There is a peak indicating -NH2 (primary amine), and at 3275 cm⁻¹, -1 There is a peak indicating -NHR (secondary amine). As shown in Figure 2, the primary amine content in the first particle is greater than the primary amine content in the third and fourth particles, and the primary amine content in the third particle is greater than the primary amine content in the fourth particle. As shown in Figure 2, the secondary amine content in the first particle is greater than the secondary amine content in the third and fourth particles, and the secondary amine content in the third particle is greater than the secondary amine content in the fourth particle.
[0054] In several embodiments, the thermal performance of adsorbed particles was analyzed using a thermogravimetric analyzer (TGA) and a differential scanning calorimeter (DSC) in a 10% CO2 gas environment. Furthermore, particle density could be calculated by measuring the volume of the particles and weighing them using a balance. The results are shown in Table 1.
[0055] [Table 1]
[0056] As can be seen from Table 1, the first type of particle has a high carbon dioxide adsorption capacity. If used directly as packing material for a carbon dioxide adsorption fixed-bed reactor, the heat dissipation due to adsorption becomes excessively high, causing localized high temperatures, which degrades the first type of particle and reduces its adsorption performance. In contrast, the second type of particle has a low heat dissipation capacity, but its carbon dioxide adsorption capacity is excessively low, which can reduce the total amount of carbon dioxide adsorbed in the reactor. Furthermore, the densities of the particles with different heat dissipation capacities are similar, approximately 0.58 to 0.72 g / cm³.3 Although it is located between these two points, this indicates that the adsorbed particles can be uniformly mixed and dispersed, and it is unlikely that the separation effect will occur due to airflow disturbances, resulting in a loss of dispersion function.
[0057] On the other hand, the first particle (particle density: 0.58~0.65 g / cm³) 3 ) 10g and silica sand (particle density: 2.65g / cm³) 3 When 10g of the first particle and the silica sand were mixed and placed in a flask, and then mixed and stirred with a glass rod, the first particle and silica sand formed separate layers within 30 seconds of stirring. This indicates that when adsorbed particles are mixed with conventional dispersion materials (e.g., silica sand, ceramic spheres, steel spheres, ceramic rings, metal rings), uniform dispersion is not possible due to an excessively large difference in particle density.
[0058] Adsorption Particle Fixed Bed Column Adsorption / Desorption Cycle Test (1):
[0059] Adsorbent compositions for Examples 1 to 10 and Comparative Examples 1 and 2 were prepared based on Table 2 and used as samples. The average heat dissipation was calculated from the ratio of adsorbed particles and the heat dissipation. For example, the heat dissipation of the first particle may be 112.9 J / g and the adsorption amount may be 2.01 mmol CO2 / g. For example, the heat dissipation of the third particle may be 76.3 J / g and the adsorption amount may be 1.21 mmol CO2 / g. For example, the heat dissipation of the fourth particle may be 63.3 J / g and the adsorption amount may be 0.84 mmol CO2 / g.
[0060] [Table 2]
[0061] A 15g sample was taken and packed into a fixed-bed column. A mixed gas of 10 vol.% CO2 and 10 vol.% H2O was used as the target gas. The adsorption conditions were a gas supply temperature of 50°C and a flow rate of 0.4 liters / minute (L / min). The desorption conditions were a desorption temperature of 100°C and a pressure of 0.2 bar. The desorption process was terminated when the CO2 concentration reached 2% to 3%. The above adsorption / desorption process constituted one cycle, and a total of 5 cycles were performed. The results are shown in Table 3.
[0062] In addition, the appearance of the samples before and after 5 adsorption / desorption cycles was observed and recorded. A "-" in the appearance section indicates that there was no clear difference in appearance.
[0063] Please refer to Figure 3, which shows the breakthrough curves according to some embodiments of this disclosure. The adsorption amount may include the working adsorption amount and the equilibrium adsorption amount. The measurement and calculation method is as follows: At the start time (t0), CO2 is added to a constant inlet concentration (C in CO2 was flowed through a fixed-bed column at a specific rate. In the initial stages, CO2 was adsorbed by the adsorbent particles, and the CO2 concentration in the output gas decreased. Over time, the adsorbent particles continued to adsorb CO2 until saturation was reached. Therefore, an increase in the CO2 concentration in the output gas was measured over time, and when the CO2 concentrations in the output gas and the input gas became equal, it indicated that adsorption had reached saturation and the adsorption reaction had reached equilibrium. As shown in Figure 3, plotting the CO2 concentration of the output gas against time yields an S-shaped curve, which is called a breakthrough curve (BTC). Breakthrough time (t b In this case, the outlet concentration is 10% of the inlet concentration (C out =0.1C in ) was the equilibrium time (t e In this case, the outlet concentration is equal to the inlet concentration (C out =C in ), and adsorption equilibrium was reached. The amount of CO2 adsorbed was equal to the inlet concentration (C in ) and inlet flow rate (Q in ) product, and outlet concentration (C out ) and outlet flow rate (Q outIt is obtained by integrating the difference between the product of ) and time. From t0 to t b The amount of adsorption integrated up to t0 is called the working adsorption amount. e The amount of adsorption integrated up to this point is called the equilibrium adsorption amount. Equilibrium adsorption recovery rate (%): Equilibrium adsorption amount at 5th time / Equilibrium adsorption amount at 1st time × 100% Operating adsorption recovery rate: 5th operating adsorption amount / 1st operating adsorption amount × 100%
[0064] [Table 3]
[0065] As shown in Tables 2 and 3, the average heat dissipation for Examples 2-5, 6-8, 9, and 10 was between 80 J / g and 105 J / g, and the operational adsorption recovery rate was greater than 80% in all cases, the equilibrium adsorption recovery rate was greater than 86% in all cases, the equilibrium adsorption amount was greater than 41 mg / g, and the equilibrium adsorption amount was greater than 28 mg / g. In Examples 2-4, 6, 7, 9, and 10, the weight of the first particle was between 28% and 88% of the total weight of the adsorbent composition, and the equilibrium adsorption recovery rate was greater than 86% in all cases, the equilibrium adsorption amount was greater than 52 mg / g, and the equilibrium adsorption amount was greater than 33 mg / g.
[0066] As shown in Tables 2 and 3, Comparative Example 1 used a single high-heat-dissipating adsorbent particle to adsorb carbon dioxide. Both its operational adsorption amount and equilibrium adsorption amount were lower than those of Examples 9 and 10, and its operational adsorption recovery rate and equilibrium adsorption recovery rate were also lower than those of Examples 9 and 10. Furthermore, Comparative Example 1 had a yellowish appearance, indicating that the amino groups in the adsorbent particle deteriorated and discolored due to high temperature. In contrast, Examples 9 and 10 mixed adsorbent particles with different heat dissipation amounts, and without the addition of additional dispersion materials, the adsorption efficiency was significantly improved, and there was no change in appearance. This indicates that adsorbent compositions containing adsorbent particles with different heat dissipation amounts can enhance the repeated adsorption / desorption performance of the material and avoid deterioration due to localized high temperatures.
[0067] As can be seen from observing Examples 1, 2, and 6, as shown in Tables 2 and 3, increasing the ratio of the third and fourth particles in the sample to 10% each can simultaneously improve both the active adsorption amount and the active adsorption recovery rate.
[0068] The adsorbent compositions of this disclosure contain particles with different heat dissipation rates, thereby increasing adsorption efficiency (e.g., equilibrium adsorption amount, working adsorption amount, equilibrium adsorption recovery rate, and working adsorption recovery rate), and / or preventing the loss of the effect of the adsorbent composition. The manufacturing method of this disclosure allows for obtaining an adsorbent composition by changing the heat dissipation rate of particles by adjusting the amino group content in different particles.
[0069] For example, the heat dissipation of the first particles can be made greater than that of the second particles, and the first and second particles can be mixed in a specific ratio to form an adsorbent composition. Therefore, by adjusting the average heat dissipation of the adsorbent composition, it is possible to avoid the generation of high temperatures in the reactor. Furthermore, it is possible to effectively avoid deterioration of the adsorbent composition, improve adsorption efficiency, and / or avoid the loss of the effect of the adsorbent composition. For example, the adsorbent composition of this disclosure can be used alone without being used in combination with a dispersion material. This can avoid the formation of layer separation in the reactor, increase the content of the adsorbent composition in the reactor, and potentially improve adsorption efficiency.
[0070] The scope of protection of this disclosure is not limited to the processes, machines, manufactures, material compositions, apparatus, methods, and steps of the specific embodiments described in the specification. Any person with ordinary skill in the art can understand existing or future-developed processes, machines, manufactures, material compositions, apparatus, methods, and steps from the content of this disclosure and use them if they perform substantially the same function or produce substantially the same results as the embodiments described herein. Accordingly, the scope of protection of this disclosure includes the aforementioned processes, machines, manufactures, material compositions, apparatus, methods, and steps. Not all embodiments or claims of this disclosure are required to achieve all the purposes, benefits, and / or features disclosed herein.
[0071] The above has provided a general overview of several embodiments so that a person with ordinary skill in the art to which this disclosure belongs can better understand the aspects of the embodiments of this disclosure. A person with ordinary skill in the art to which this disclosure belongs will understand that they can design or modify other processes and structures based on the embodiments of this disclosure to achieve the same objectives and / or advantages as the embodiments described herein. A person with ordinary skill in the art to which this disclosure belongs will also understand that such equivalent processes and structures will not exceed the spirit and scope of this disclosure, and they can make various changes, substitutions and alternatives without being contrary to the spirit and scope of this disclosure. [Explanation of Symbols]
[0072] S1, S2, S3... Step
Claims
1. Adsorbent composition, A first base particle modified with an amino group, having a first heat dissipation amount, is provided in a quantity of 100 parts by weight. A second base particle modified with amino groups and epoxy groups, and having a second heat dissipation capacity, is provided in a quantity of 3 to 450 parts by weight, Includes, An adsorbent composition in a gas environment of 10% carbon dioxide by volume and 90% inert gas by volume, wherein the first heat dissipation is greater than 90 J / g and 130 J / g or less, and the second heat dissipation is 35 J / g or more and 90 J / g or less.
2. The adsorbent composition according to claim 1, wherein the content of amino groups in the first particle is greater than the content of amino groups in the second particle.
3. The second particle described above, In a gas environment of carbon dioxide at a volume percentage of 10% and an inert gas at a volume percentage of 90%, a third particle having a third heat dissipation amount greater than 65 J / g and less than or equal to 90 J / g is provided in an amount of 0 to 330 parts by weight. A fourth particle having a heat dissipation amount different from the third heat dissipation amount, in a gas environment of carbon dioxide at a volume percentage of 10% and an inert gas at a volume percentage of 90%, wherein the fourth heat dissipation amount is 35 J / g or more and less than 65 J / g, is present in an amount of 0 to 150 parts by weight. Includes, The adsorbent composition according to claim 1, wherein the third particle and the fourth particle are not simultaneously present in amounts of 0 parts by weight.
4. The adsorbent composition according to claim 3, wherein the amino group content in the third particle is greater than the amino group content in the fourth particle.
5. The adsorbent composition according to claim 1, wherein in a gas environment of 10% by volume carbon dioxide and 90% by volume inert gas, the average heat dissipation of the adsorbent composition is 65 J / g or more and 120 J / g or less.
6. A method for producing an adsorbent composition, The first step is to prepare a first base particle modified with an amino group, having a first heat dissipation amount, and having a first heat dissipation amount greater than 90 J / g and less than or equal to 130 J / g in a gas environment of 10% by volume carbon dioxide and 90% by volume inert gas, The steps include: preparing second base particles modified with amino groups and epoxy groups, having a second heat dissipation rate, and having a second heat dissipation rate of 35 J / g or more and 90 J / g or less in a gas environment of 10% by volume carbon dioxide and 90% by volume inert gas; The steps include mixing the first particles and the second particles to obtain the adsorbent composition, Includes, The first particle is 100 parts by weight, The amount of the second particle is 3 to 450 parts by weight. Manufacturing method.
7. The step of preparing the first particle is, The steps include: mixing the first base particles with a metal chelating agent to obtain a first powder; A step of mixing a material containing amino groups with the first powder to obtain a second powder, The steps include mixing the second powder and the adhesive to obtain the first particles, Includes, The manufacturing method according to claim 6, wherein the ratio of the weight of the amino group-containing material to the weight of the first base particles (weight of the amino group-containing material / weight of the first base particles) is 0.5 to 0.
75.
8. The step of preparing the second particle is, The steps include: mixing the second base particles and the metal chelating agent to obtain a third powder; The steps include: mixing the material containing the amino group and the epoxide to obtain a solution; The steps include mixing the solution and the third powder to obtain a fourth powder, The steps include mixing the fourth powder and the adhesive to obtain the second particles, Includes, The manufacturing method according to claim 7, wherein the ratio of the weight of the epoxide to the weight of the material containing the amino group (weight of the epoxide / weight of the material containing the amino group) is 0.01 to 0.
8.
9. The manufacturing method according to claim 8, wherein the ratio of the weight of the amino group-containing material to the weight of the second base particles (weight of the amino group-containing material / weight of the second base particles) is 0.2 to 0.65.
Citation Information
Patent Citations
Renewable Adsorbents for Modified Amines on Solid Supports
JP2018509280A
Adsorbent composition, its manufacturing method and application
JP2023543823A
Polymeric amine based carbon dioxide adsorbents
US20180008958A1
Functionalised hydrogels
WO2022183244A1
Carbon dioxide adsorbent
WO2023100986A1